Balancing pH and yield: exploring itaconic acid production in Ustilago cynodontis from an economic perspective - Philipp Ernst; Katharina Maria Saur; Robert Kiefel; Paul-Joachim Niehoff; Ronja Weskott; Jochen Büchs; Andreas Jupke; Nick Wierckx (Biotechnology for Biofuels and Bioproducts, 2024)
Abstract Background Itaconic acid is a promising bio-based building block for the synthesis of polymers, plastics, fibers and other materials. In recent years, Ustilago cynodontis has emerged as an additional itaconate producing non-conventional yeast, mainly due to its high acid tolerance, which significantly reduces saline waste coproduction during fermentation and downstream processing. As a result, this could likely improve the economic viability of the itaconic acid production process with Ustilaginaceae. Results In this study, we characterized a previously engineered itaconate hyper-producing Ustilago cynodontis strain in controlled fed-batch fermentations to determine the minimal and optimal pH for itaconate production. Under optimal fermentation conditions, the hyper-producing strain can achieve the theoretical maximal itaconate yield during the production phase in a fermentation at pH 3.6, but at the expense of considerable base addition. Base consumption is strongly reduced at the pH of 2.8, but at cost of production yield, titer, and rate. A techno-economic analysis based on the entire process demonstrated that savings due to an additional decrease in pH control reagents and saline waste costs cannot compensate the yield loss observed at the highly acidic pH value 2.8. Conclusions Overall, this work provides novel data regarding the balancing of yield, titer, and rate in the context of pH, thereby contributing to a better understanding of the itaconic acid production process with Ustilago cynodontis, especially from an economic perspective.